2020
DOI: 10.3390/medicina56080402
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Indicators in Patients Operated on for Breast Cancer in Relation to the Type of Surgery—A Retrospective Cohort Study of Women in Serbia

Abstract: Background and objectives: Quality of life (QoL) after breast cancer surgery is an important public health issue. The aim of this study was to determine the relationship between the levels of perceived quality of life in patients operated on for breast cancer in relation to the type of surgery, using the standardized questionnaires. Materials and Methods: We assessed 425 women after surgery for breast cancer. The assessment included the application of the WHOQOL-bref (The World Health Organization Quality of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
10
1
2
Order By: Relevance
“…The education level and employment status of BC participants have been found to have a positive in uence on QOL as it relates to physical and mental health as well as emotional well-being and vitality, respectively. Similarly, previous studies found signi cantly higher HRQOL scores among BC participants who had higher school education [43,[49][50][51], and were employed [31,43,[51][52][53][54]. Unlike our results, Ahmed et al, found unemployment BC survivors reported positive QOL perceptions related to role emotional, emotional well-being, and social function, but lower perceptions regarding physical function [21].…”
Section: Discussioncontrasting
confidence: 50%
“…The education level and employment status of BC participants have been found to have a positive in uence on QOL as it relates to physical and mental health as well as emotional well-being and vitality, respectively. Similarly, previous studies found signi cantly higher HRQOL scores among BC participants who had higher school education [43,[49][50][51], and were employed [31,43,[51][52][53][54]. Unlike our results, Ahmed et al, found unemployment BC survivors reported positive QOL perceptions related to role emotional, emotional well-being, and social function, but lower perceptions regarding physical function [21].…”
Section: Discussioncontrasting
confidence: 50%
“…It has also been scientifically proven that the type of surgical intervention used constitutes a relevant factor for the BI of women affected by this disease. When the treatment implies a surgical process, the situation becomes harder, since the woman must face a significant loss of her body [ 39 , 40 , 41 , 42 ]. In this regard, BC women who have had a mastectomy can show emotional instability, diminished physical attractiveness perception, reduction in self-esteem, and partner relationship disturbances [ 11 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mean scores of the four WHOQOL-BREF domains and the perception of global QoL measured in BCSs vary widely between studies [ 7 , 15 18 , 33 ]. These differences may be due to the fact that these studies were conducted in different countries/regions, in different living environments, among people of different cultures, with different education and financial levels, different age and time periods since cancer diagnosis or surgery; and presenting above all unadjusted mean scores on specific domains of WHOQOL-BREF.…”
Section: Discussionmentioning
confidence: 99%